PENGARUH EKUITAS MEREK ( BRAND EQUITY ) TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE BLACKBERRY (Studi pada Mahasiswa Program S1 Jurusan Administrasi Bisnis Fakultas Ilmu Sosial dan Ilmu Politik) - Harry Christian Barus; Nawazirul Lubis; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2015)
This research aim is to know the influence of the brand awareness, perceived quality , brand associations , brand loyalty to the Purchasing Decision of Blackberry Smartphone. The type of research that used is explanatory research which is using population of a number of active student from Undergraduate Program of Bussiness Administration .Population that is used is about 88 respondents with sample  taken method using purposive sampling ( sample taken method using some considerations). The technique to get data in this research is interview and questioner as the collecting data instrument.The result of the statistic test and F test known that the brand awareness , perceived quality , brand association , and brand loyalty simultaneously have positive influence and significant to the purchasing decision. This can be seen from the result test of determination coefficient influence of brand awareness , perceived quality , brand association , and brand loyalty simultaneously have positive influence and significant to the purchasing decision as big as 0,604 or 60,4 %.